Financial modelling in turbulent scenarios: A didactic for the financial valuation of companies and projects (2022)
The actual professional needs to process large volumes of real information from companies and projects, to test and to validate various solution scenarios for the most successful decision making in difficult situations. This proposal summarizes the experience of several years of university teaching in finance courses, undergraduate and postgraduate, of mixed groups of students from the Faculty of Engineering and Business School of the Universidad Tecnológica de Bolívar, in Cartagena, Colombia. After working with various didactic approaches, you get to understand the importance of the interaction with theoretical and practical elements that enable the development of analytical skills, systemic and critical thinking, among others, based on the review of the use of spreadsheets, sensitivity analysis and simulation tools, for modeling projections and financial valuation of a company or project. © 2022 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.